A Systemic Review of Various Multifactor Authentication Schemes - Singh, Charanjeet; Singh, Tripat Deep (International Journal of Computer Sciences and Engineering, 2019)
With the advancement in information technology, use of cloud has gained rapid acceptance. The usage of such public infrastructures not only increase the risk of data theft but also raise concerns for providing better security to data and resources. One aspect of security deals with authentication method that is used to gain access to the resources over these shared platforms. Strong authentication technique lays foundation for data protection. Simple username-password schemes (single factor) have been proved to be insecure and insufficient in providing secured access thereby urging the need for multifactor authentication (MFA) schemes. Multifactor authentication schemes not only provide an extra layer of security but are also robust against various types of network attacks. The objective of this paper is to review the various multifactor authentication schemes and models that are used to verify the identity of users. This paper highlights the technique, multi-layer cybersecurity strategy, strengths and weaknesses of various schemes with the view to enhance security.